PENGARUH ONLINE CUSTOMER RATING, HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN TRANSPORTASI ONLINE MAXIM DALAM PERSPEKTIF BISNIS ISLAM (STUDI PADA PENGGUNA MAXIM DI BANDAR LAMPUNG) - Dera Yulia Irawan; Muhammad Iqbal; Is Susanto (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the influence of online customer ratings, prices and service quality on customer loyalty in Maxim online transportation in Bandar Lampung and to determine the influence of online customer ratings, prices and service quality on customer loyalty in Maxim online transportation from an Islamic business perspective. This study uses quantitative methods and data collection using questionnaires. The population in this study were Maxim users in Bandar Lampung, with a sample of 96 respondents obtained through purposive sampling techniques. Data was processed using SmartPLS version 4. The results of this study are that Online Customer Rating does not have a significant effect on Customer Loyalty. This can be seen from the original sample value, namely the original sample is 0.146, the t-statistic is 1.166 <1.96 and the p-values ​​are 0.123> 0.05. Furthermore, Price has a positive and significant effect on Customer Loyalty. This can be seen from the original sample value, namely the original sample is 0.482, the t-statistic value is 2.816> 1.96 and the p-values ​​are 0.002 <0.05. Furthermore, Service Quality has a positive and significant effect on Customer Loyalty. This can be seen from the original sample value, namely the original sample is 0.300, the t-statistic value is 2.262> 1.96 and the p-values ​​are 0.013 <0.05. In the perspective of Islamic business on Online Customer Rating, Price and Service Quality affect Customer Loyalty. This is explained by the value of the Customer Loyalty determination coefficient from an Islamic business perspective of 0.659 or 65.9% and the remainder, namely 34.1%, is explained by other constructs or influences outside the research conducted.